Quinolone-resistant Escherichia coli at the interface between humans, poultry and their shared environment- a potential public health risk - Mabel Kamweli Aworh; Jacob K. P. Kwaga; Rene S. Hendriksen; Emmanuel C. Okolocha; Erin Harrell; Siddhartha Thakur (BMC, 2023)
Abstract Background Commensal Escherichia coli residing in the guts of humans and animals are reservoirs of multidrug resistance (MDR) genes, including quinolone resistance genes, in humans and poultry. This study aimed to characterize quinolones resistance in E. coli recovered from poultry workers, chickens, and poultry farm/market environments in Abuja, Nigeria. Methods This was a cross-sectional study conducted between December 2018 and April 2019 comprising poultry workers, chickens and their poultry farm/market environments. This study characterized E. coli isolates from stool, faecal and environmental samples using antimicrobial susceptibility testing and whole-genome sequencing methods. Core-genome multilocus sequences-based phylogeny was used to determine the relatedness between quinolone-resistant E. coli isolates. Data were analyzed using descriptive statistics. Results Of 110 E. coli isolates, quinolone-resistant phenotypes were observed in 68.2% (n = 75) isolates. Whole-genome sequencing detected plasmid-mediated quinolone resistance (PMQR) genes in 63.6% (n = 70) isolates. The most prevalent PMQR gene detected in 56 of these 70 E. coli isolates was qnrS1, followed by qnrB19 in 14 isolates and aac(6')-lb-cr in two isolates. Fifteen ciprofloxacin and 19 nalidixic acid-resistant isolates respectively showed double mutations in the quinolone-resistance determining regions (QRDRs) of gyrA, with single or double mutations in parC, and a single mutation in parE. The most prevalent amino-acid substitutions observed were S83L + D87N in gyrA (46.5%, n = 20), S80I in parC (51.2%, n = 22) and S458A in parE (14%, n = 6). About 2.9% (2/70) of PMQR isolates were extended-spectrum beta-lactamase (ESBL) producers while 2.9% (2/70) had plasmid-mediated colistin resistance (PMCR) genes. Conclusions PMQR genes were prevalent in E. coli isolates recovered from healthy humans, chickens and poultry farm/market environments. PMCR genes (mcr-1.1) occurred in PMQR-positive isolates recovered from manure and drinking water originating from poultry farm/market environments. It was found that the gene encoding ESBL coexisted with qnrS-positive isolates of human and avian origin. Horizontal transfer of PMQR genes among E. coli isolates in the human-poultry-environment interface has public health implications for the spread of antimicrobial resistance. Relevant government agencies should enforce regulations to restrict the use of critically important antimicrobials in poultry production.